Simulation of a synchronized methodology for MR-based electromechanical property imaging during transcranial electrical stimulation - Flé, Guillaume; Van Houten, Elijah; Gilbert, Guillaume; Cloutier, Guy (Frontiers in Physics, 2024)
Recent investigations into the biomechanics of the brain have unveiled alteration in tissue stiffness triggered by external stimuli. For instance, visual stimulation effects can be measured in elasticity images of the cortex generated by functional magnetic resonance elastography (MRE). Such a mechanical characterization method combined with non-invasive brain stimulation (NIBS), a technique that seeks to selectively modulate particular parts of the brain using weak electrical currents, has the potential to influence research on various neurological disorders.